Noise levels in neonatal intensive care unit and use of sound absorbing panel in the isolette - BİLGEN, HÜLYA SELVA (ELSEVIER IRELAND LTD, 2009)
Objective: The purposes of this study were to measure the noise level of a busy neonatal intensive care unit (NICU) and to determine the effect of sound absorbing panel (SAP) on the level of noise inside the isolette. Methods: The sound pressure levels (SPL) of background noise, baby crying, alarms and closing of isolette's door/portholes were measured by a 2235-Bruel&Kjaer Sound Level Meter. Readings were repeated after applying SAP (3D pyramidal shaped open cell polyurethane foam) to the three lateral walls and ceiling of the isolette. Results: The median SPL of background noise inside the NICU was 56 dBA and it decreased to 47 dBA inside the isolette. The median SPL of monitor alarms and baby crying inside the isolette were not different than SPL measured under radiant warmer (p > 0.05). With SAP, the median SPL of temperature alarm inside the isolette decreased significantly from 82 to 72 dBA, monitor alarm from 64 to 56 dBA, porthole closing from 81 to 74 dBA, and isolette door closing from 80 to 68 dBA (p < 0.01). There was a significant reduction in the noise produced by baby crying when SAP was used in the isolette (79 dBA vs 69 dBA, respectively) (p < 0.0001). There was also significant attenuation effect of panel on the environmental noise. Conclusions: The noise level in our NICU is significantly above the universally recommended levels. Being inside the isolette protects infants from noise sources produced outside the isolette. However, very high noises are produced inside the isolette as well. Sound absorbing panel can be a simple solution and it attenuated the noise levels inside the isolette. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Noise levels; Sound absorbing panel; Noise reduction; RISK